Realtime face matching and gender prediction based on deep learning - Thongchai Surinwarangkoon; Vinh Truong Hoang; Ali Vafaei-Zadeh; Hayder Ibrahim Hendi; Kittikhun Meethongjan (Institute of Advanced Engineering and Science, 2023)
Face analysis is an essential topic in computer vision that dealing with human faces for recognition or prediction tasks. The face is one of the easiest ways to distinguish the identity people. Face recognition is a type of personal identification system that employs a person’s personal traits to determine their identity. Human face recognition scheme generally consists of four steps, namely face detection, alignment, representation, and verification. In this paper, we propose to extract information from human face for several tasks based on recent advanced deep learning framework. The proposed approach outperforms the results in the state-of-the-art.